Pembelajaran Menulis Naskah Drama dengan Strategi Menulis Terbimbing - Agus Mulia (Balai Bahasa Sumatera Utara, 2021)
The main purpose of writing a drama script is to be read by the reader and as a guide for people who will play a drama. Drama scripts which follow the rules of writing, will make the readers become easier to understand the contents of the script. The main object of this research is the product of learning guidelines for writing drama scripts that have been practiced for participants in the drama script writing class (KMND). The research subjects were 25 KMND students at the Balai Bahasa Sumatera Utara (North Sumatera Language Center). The results of this study were drama manuscripts written by the participants of the KMND class which were assessed and analyzed based on the structure and elements of the drama script. Data was collected using the following methods: (1) observation, (2) interviews, (3) questionnaires, and (4) documentation. Data analysis includes data reduction activities, data presentation, and drawing conclusions.